Beam Steering Using Active Artificial Magnetic Conductors: A 10-Degree Step Controlled Steering - Juan Andres Vasquez-Peralvo (IEEE Access, 2020)
An Active Artificial Magnetic Conductor (AAMC) is presented to steer the radiation pattern of a printed dipole working at 2 GHz. The elements that generates the phase shift are a set of Varactor Diodes, which are characterized using its spice model in order to obtain a phase shift - capacitance mapping. Overall beam steering of +/40° with a step size of 10° is achieved. A circuit model that describes any multilayer substrate AAMC unit cell, which uses fist form of Foster's theorem along with transmission line theory, is proposed. Our work is suitable to be used as low profile antenna; for example, street furniture antennas, which are located on the facades of houses or buildings, so that they can be visually mixed up with signs or advertisements. Simulations have been validated using a prototype consisting of an array of 22 × 14 AAMC elements; the overall structure measures 1.9λ0 × 1.21λ0. This reflector will generate a phase gradient in its columns, which will modify the reflection angle of an incident electromagnetic wave in the H-Plane. Beam switching control has been achieved using suitably amplified LPF PWM signals generated by two Arduino modules. A printed dipole with a Fractional Bandwidth of 17% is designed and manufactured to illuminate the structure at a distance λ0/4 above the surface. Far-field radiation patterns and reflection coefficients have been measured in an anechoic chamber using a spherical system. These compare favorably with simulations performed using the Time Domain solver in CST Microwave Studio.